On the fatigue behavior of duplex and high-strength welded cruciform joints - Karabulut, B; Rossi, B (Elsevier, 2021)
This paper presents outcome of a research which investigates the fatigue behaviour of duplex stainless steel grade (EN 1.4162) via cyclic tests on welded cruciform joints and base plates. A database of experimental tests for similar high-strength steel details was also collated from the literature. The obtained experimental S-N curve was then compared to the current European design ones and re-evaluated according to the hot spot stress method. A good agreement was observed between the studied detail performance and the collated reference data. Improvement to the fatigue design rules for the studied duplex and similar high-strength steel details is then proposed.